Systemic design and control of switching synchronous motor dedicated to electric car motorization. (3rd July 2017) - Tounsi, Souhir
Abstract: In this paper, we present a design and control methodology of an innovated structure of switching synchronous motor with reduced production cost. The control strategy is based on the pulse width modulation technique imposing currents sum of a continuous value and a value having a shape varying in phase opposition with respect to the variation of the inductances. This control technology can greatly reduce vibration of the entire system due to the strong fluctuation of the torque developed by the engine, generally characterizing switching synchronous motors. A systemic design and modeling program is developed. This program is validated following the implementation and the simulation of the control model in the simulation environment Matlab-Simulink. Simulation results are with good scientific level and encourage subsequently the industrialization of the global system.